Ultrasound assessment of muscle mass in response to exercise training in chronic kidney disease: a comparison with MRI - Gould, Douglas W. (2019)
Chronic kidney disease (CKD) is a catabolic condition associated with muscle wasting and dysfunction, which associates with morbidity and mortality. There is a need for simple techniques capable of monitoring changes in muscle size with disease progression and in response to interventions aiming to increase muscle mass and function. Ultrasound is one such technique; however, it is unknown how well changes in muscle cross-sectional area (CSA) measured using ultrasound relate to changes in whole muscle volume measured using magnetic resonance imaging. We tested whether rectus femoris CSA (RF-CSA) could be used as a valid indication of changes in quadriceps muscle volume as a single measure of muscle size and following a 12 week exercise intervention that resulted in muscle hypertrophy.